Establishment of linkage on all financial actors in the financial ecosystem a technology foresight in financial innovation in the Philippines in year 2022 - Cabrera, Dancelle Daine Roman; Cabrera, Dancelle Daine Roman (Quezon City University of the Philippines Diliman, 2017)
The age of technology has been rapidly accelerating in the Philippines and has immensely create a great dissolution to the conventional ways of life per se and shape it into a totally different perspective. There are several startup groups and companies developing tech - based solutions for consumers in emerging markets and has seen growing opportunities in the country today. They view the country as a good testing ground for tech products and services having potential in a global scale. In this study, the researcher focused on one of its application in the perspective of the financial ecosystem. The motivation of the researcher's study is to realize how to unlock an economic opportunity for the poor and to apprehend the role of technology in innovating the financial system in the Philippines.
The study focuses on three financial actors-financial inclusion, financial services and financial technology. These three core entities build the industry of financial sector. In establishing linkage with these three main actors in the financial ecosystem, the goal of the government and the private sectors to reach the unbanked society will be delivered in order to empower the Filipinos toward financial welfare, have a sustainable financial access in all regions in the Philippines and experience financial capability. The goal now is to bank the unbanked.
The technology foresight through scenario building focuses on 5-year duration (2017-2022) aligned in parallel to Philippine Development Plan of 2017-22 for the development of linkage in all financial actors in creating sustainable inclusive financing and achieve success of financial innovation in the financial industry.
The scenario assumes that the Bangko Sentral ng Pilipinas will create a body that will create regulation and policies in strengthening and uniting all financial actors in the Philippines. As they aim to be a world-class monetary authority and a catalyst for a globally competitive economy, they are striving to deliver a financial system that delivers a high quality of life for all Filipinos.
Philippines took the next greatest share of deals at 14% in 2017 FinTech deal share in the Southeast Asia. In it is projected that we can hit almost 30 percent or more by year 2022 if we are to reference the percentage of FinTech growth from 2012-2017. Possibly a 50 percent markup can be achieve given that more venture capitalist will invest in the country to enhance the propositions of existing documents.
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: Financial services industry; Technological foresight